The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00170-011-3604-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electrode force, welding current and welding time on the resistance spot weldability of pure titanium

Abstract: In this study, commercially pure titanium sheets (American Society for Testing and Materials grade 2) were welded by resistance spot welding at various welding parameters. The welded joints were subjected to tensileshearing tests in order to determine the strength values. In addition, the hardness and microstructural examinations were carried out in order to examine the influence of welding parameters on the welded joints. The experimental results showed that increasing electrode force, welding current and wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 24 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Resistance spot welding is the most widely used method in the joining of thin metal sheets due to its high effeciency and high degree of automation, in which a small weld is formed between two metal workpieces through localized melting due to interfacial resistance heating. The present study revealed that the spot resistance welding of titanium alloys to themselves and to other materials was successfully performed [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. Especially, the interfacial microstructure mainly consisted of TiAl 3 intermetallics when the the titanium alloys were spot resistance welded to aluminium alloys [ 116 , 120 ], which indicated the possibility of spot resistance welding of titanium aluminides.…”
Section: Joining Of Titanium Aluminides By Other Methodsmentioning
confidence: 99%
“…Resistance spot welding is the most widely used method in the joining of thin metal sheets due to its high effeciency and high degree of automation, in which a small weld is formed between two metal workpieces through localized melting due to interfacial resistance heating. The present study revealed that the spot resistance welding of titanium alloys to themselves and to other materials was successfully performed [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. Especially, the interfacial microstructure mainly consisted of TiAl 3 intermetallics when the the titanium alloys were spot resistance welded to aluminium alloys [ 116 , 120 ], which indicated the possibility of spot resistance welding of titanium aluminides.…”
Section: Joining Of Titanium Aluminides By Other Methodsmentioning
confidence: 99%
“…As a traditional welding technique, resistance spot welding could isolate atmospheric gases effectively through electrode force implementation. Kaya and Kahraman [4] found that resistance spot welding was an effective welding process for 1.5 mm pure titanium sheets.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in microhardness is ascribed to the different microstructures. The formation of martensite increases the microhardness in the WN 15 and grain coarsening softens the HAZ. As discussed above, because of the heat concentration that occurs when microjoining ultrathin foils, no obvious phase transformation takes place in the HAZ compared with LSRSW.…”
Section: Results and Analysismentioning
confidence: 99%